Research anthology on environmental and societal well-being considerations in buildings and architecture (Engineering Science Reference, 2021)
"This book of contributed chapters focuses on different aspects of how the built environment is being constructed to purposefully enhance societal well-being while also maintaining green standards for environmental sustainability"--